(untitled) (The Pakistan Development Review, 2004)
The effects of devaluation or depreciation on the trade balance of a country are usually examined by the Marshall-Lerner [ML] condition, which states that if the sum of the absolute values of imports and exports demand price elasticities is greater than one, devaluation is expected to improve the trade balance of a country. Some Structural Adjustment Reforms were started with the help of IMF and World Bank in 1982-83 with the objective of improving the efficiency of the economy by increasing the role of the private sector. The reforms included the delinking of the Rupee from US dollar in January 1982, price deregulation of a large number of products, denationalisation of industry, imports liberalisation and export expansion [Khan (1994)]. The successive governments have taken a number of steps to pursue an extensive liberalisation of the trade regime in addition to taking a number of export measures. Exchange and payment reforms were also implemented [Pakistan (1991-92)].